Restless AMPA receptors: implications for synaptic transmission and plasticity - Lüscher, Christian (2001)
A central assumption in neurobiology holds that changes in the strength of individual synapses underlie changes in behavior. This concept is widely accepted in the case of learning and memory where LTP and LTD are the most compelling cellular models. It is therefore of great interest to understand, on a molecular level, how the brain regulates the strength of neuronal connections. We review a large body of evidence in support of the very straightforward regulation of synaptic strength by changing the number of postsynaptic receptors, and discuss the molecular machinery required for insertion and removal of AMPA receptors.